The Effect of Work Culture and Reward on Military Education Professional Commitments at The Middle of The Center of The Commando for The Development of the Doctrines of Education and Training of the TNI Al (KODIKLATAL) Surabaya - R Anang Dwikuncoro; Makruf Akbar; Suparno Eko Widodo (STAI Miftahul Ula Nganjuk, 2019)
The purpose of this study was to determine the effect of work culture and reward on military education professional commitments at the middle of the center of the commando for the development of the doctrines of education and training of the TNI AL (KODIKLATAL) Surabaya. The research used is a survey with a causal design. The number of respondents was set at 160 educators, the sampling technique was done by simple random sampling from 265 organic educators at the level of Middle Officers who were lecturing in Kobangdikal, Bumi Moro, Surabaya.